ISPO introduction program for independent smallholders: Initial steps towards mandatory ISPO 2025 - Riantri Barus; Diana Chalil; Rulianda Purnomo Wibowo (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The government, through Peraturan Presiden RI Nomor 44 Tahun 2020, mandates Indonesian Sustainable Palm Oil (ISPO) certification for smallholder farmers within five years of its enactment. However, by December 2022, only 32 farmer groups had achieved ISPO certification. The Gunung Ambat Farmers Group, which has already received funds from the PSR program, is one of the independent farmer groups with the potential to acquire ISPO accreditation. Yet, members' understanding of this certification remains low due to a lack of socialization or training from the government or other entities. This initiative aims to promote the regulation and provide training on the concepts and requirements for ISPO certification. Activities include administering questionnaires to assess knowledge, conducting training sessions, engaging in puzzle games, and practicing the documentation of farming activities. The results indicate significant improvements in farmers' understanding before and after the training. Initially, farmers had no knowledge of ISPO certification; however, post-training, over 70 percent of participants understood the certification, with an average of 35 percent comprehending its principles and criteria. Participants are also encouraged to document their farming progress, enhancing their skills in farming business documentation and administrative tasks.